Resin composition and molded article

By using specific ethylene-vinyl acetate copolymers and hydrogenated block copolymers in the resin composition, the problem of difficult balance between dry grip and wet grip in the prior art is solved, and excellent grip performance in applications such as soles and tires for footwear are achieved.

CN115135714BActive Publication Date: 2025-04-18KURARAY CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202180017320.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-27
Filing Date
2021-02-25
Publication Date
2025-04-18
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve excellent balance between dry grip and wet grip in applications such as soles and tires for footwear.

Method used

The resin composition is formed by using an ethylene-vinyl acetate copolymer and a hydrogenated block copolymer by a specific compounding amount. The hydrogenated block copolymer contains polymer blocks, respectively, structural units derived from aromatic vinyl compounds and farnesene.

Benefits of technology

It realizes molded bodies with excellent dry and wet grip, and is suitable for soles and tires for footwear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

Provided are a resin composition capable of providing a molded body having excellent dry grip and wet grip, and a molded body using the resin composition. A resin composition comprising an ethylene-vinyl acetate copolymer (I) and a hydrogenated block copolymer (II), wherein the hydrogenated block copolymer (II) is a hydrogenated product of a block copolymer (P) comprising a polymer block (A) and a polymer block (B), wherein the polymer block (A) comprises a structural unit derived from an aromatic vinyl compound, and the polymer block (B) comprises 1 to 100% by mass of a structural unit (b1) derived from farnesene and 99 to 0% by mass of a structural unit (b2) derived from a conjugated diene other than farnesene, wherein the hydrogenation rate of carbon-carbon double bonds in the structural unit derived from the conjugated diene in the block copolymer (P) is 70 mol% or more, and the content of the ethylene-vinyl acetate copolymer (I) in the resin composition is 40 to 95% by mass, and the content of the hydrogenated block copolymer (II) is 5 to 60% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition containing at least an ethylene-vinyl acetate copolymer and a hydrogenated block copolymer having a structural unit derived from farnesene, and a molded article using the resin composition. Background Art

[0002] Rubber compositions obtained by mixing thermoplastic elastomers such as styrene elastomers and olefin elastomers with various rubbers are used in a wide range of fields such as soles for footwear, various tires, building materials such as packaging, and machine parts due to their excellent mechanical properties and flexibility. However, rubber compositions containing thermoplastic elastomers are prone to slippage due to the adhesion of moisture, which is a problem that they are highly dangerous, particularly in applications such as soles for footwear and various tires.

[0003] Therefore, studies have been conducted to improve the wet grip performance of a rubber composition containing a thermoplastic elastomer and a rubber component.

[0004] For example, resin compositions that limit the number average molecular weight of thermoplastic elastomers and the glass transition temperature of rubber components, or contain adhesion-imparting resins and hydrogenated block copolymers have been proposed (e.g., Patent Documents 1 to 8). In addition, resin compositions containing hydrogenated block copolymers that include polymer blocks containing structural units derived from farnesene have been proposed (e.g., Patent Document 9).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: U.S. Patent Application Publication No. 2013 / 0086822

[0008] Patent Document 2: International Publication No. 2006 / 121069

[0009] Patent Document 3: Japanese Patent Application Publication No. 2017-39819

[0010] Patent Document 4: Japanese Patent Application Publication No. 2016-210937

[0011] Patent Document 5: Japanese Patent Application Publication No. 2014-189697

[0012] Patent Document 6: Japanese Patent Application Publication No. 2014-520017

[0013] Patent Document 7: Japanese Patent Application Publication No. 2004-75882

[0014] Patent Document 8: Japanese Patent Application Publication No. 2003-292672

[0015] Patent document 9: Japanese Patent Publication No. 2019-26826. Summary of the invention

[0016] Problem that the invention aims to solve

[0017] However, the techniques disclosed in Patent Documents 1 to 8 cannot provide a resin composition having an excellent balance between dry grip and wet grip, and further improvement is required. It should be noted that Patent Documents 1 to 8 do not describe a block copolymer comprising a polymer block containing a structural unit derived from an aromatic vinyl compound and a polymer block containing a structural unit derived from farnesene, and a hydrogenated product thereof.

[0018] In addition, although the resin composition disclosed in Patent Document 9 is excellent in the balance between dry grip performance and wet grip performance, further improvement is required.

[0019] Therefore, an object of the present invention is to provide a resin composition capable of providing a molded product having excellent dry grip properties and wet grip properties, and a molded product using the resin composition.

[0020] Solutions to Solve Problems

[0021] The present inventors have conducted intensive studies in view of the above problems and have found that the above problems can be solved by using an ethylene-vinyl acetate copolymer and a specific hydrogenated block copolymer in specific blending amounts.

[0022] That is, the present invention relates to the following [1] to

[11] .

[0023] [1] A resin composition comprising an ethylene-vinyl acetate copolymer (I) and a hydrogenated block copolymer (II), wherein:

[0024] The hydrogenated block copolymer (II) is a hydrogenated product of a block copolymer (P) comprising a polymer block (A) and a polymer block (B), wherein the polymer block (A) comprises a structural unit derived from an aromatic vinyl compound, and the polymer block (B) comprises 1 to 100% by mass of a structural unit (b1) derived from farnesene and 99 to 0% by mass of a structural unit (b2) derived from a conjugated diene other than farnesene, wherein the hydrogenation rate of carbon-carbon double bonds in the structural unit derived from the conjugated diene in the block copolymer (P) is 70 mol% or more,

[0025] The resin composition contains the ethylene-vinyl acetate copolymer (I) in an amount of 40 to 95% by mass, and the hydrogenated block copolymer (II) in an amount of 5 to 60% by mass.

[0026] [2] The resin composition according to [1] above, wherein the biomass ratio is 4 to 70% by mass.

[0027] [3] The resin composition according to [1] or [2], wherein the content of the structural unit derived from vinyl acetate in the ethylene-vinyl acetate copolymer (I) is 5 to 60% by mass.

[0028] [4] The resin composition according to any one of [1] to [3], wherein the aromatic vinyl compound is styrene.

[0029] [5] The resin composition according to any one of [1] to [4], wherein the conjugated diene other than farnesene is at least one selected from butadiene, isoprene, and myrcene.

[0030] [6] The resin composition according to any one of [1] to [5], wherein a mass ratio [(A) / (B)] of the polymer block (A) to the polymer block (B) is 10 / 90 to 40 / 60.

[0031] [7] The resin composition according to any one of [1] to [6], wherein the hydrogenated block copolymer (II) further comprises a polymer block (C) composed only of structural units derived from a conjugated diene other than farnesene.

[0032] [8] The resin composition according to any one of [1] to [7], wherein the SP value of the ethylene-vinyl acetate copolymer (I) is 4.0 to 10.0 (cal / cm 3 ) 1 / 2 The SP value of the hydrogenated block copolymer (II) is 6.0 to 10.0 (cal / cm 3 ) 1 / 2 .

[0033] [9] The resin composition according to any one of [1] to [8], wherein the peak molecular weight of the hydrogenated block copolymer (II) is 50,000 to 500,000.

[0034]

[10] The resin composition according to any one of [1] to [9], wherein the peak molecular weight of the polymer block (A) is 5,000 to 100,000.

[0035]

[11] A molded article, at least a portion of which is formed using the resin composition described in any one of [1] to

[10] .

[0036] Effects of the Invention

[0037] According to the present invention, there can be provided a resin composition capable of providing a molded product having excellent dry grip properties and wet grip properties, and a molded product using the resin composition. DETAILED DESCRIPTION

[0038] [Resin composition]

[0039] The resin composition of the present invention comprises an ethylene-vinyl acetate copolymer (I) and a hydrogenated block copolymer (II), wherein the hydrogenated block copolymer (II) is a hydrogenated product of a block copolymer (P) comprising a polymer block (A) and a polymer block (B), wherein the polymer block (A) comprises a structural unit derived from an aromatic vinyl compound, and the polymer block (B) comprises 1 to 100% by mass of a structural unit (b1) derived from farnesene and 99 to 0% by mass of a structural unit (b2) derived from a conjugated diene other than farnesene, wherein the hydrogenation rate of carbon-carbon double bonds in the structural unit derived from the conjugated diene in the block copolymer (P) is 70 mol% or more, and the content of the ethylene-vinyl acetate copolymer (I) in the resin composition is 40 to 95% by mass, and the content of the hydrogenated block copolymer (II) is 5 to 60% by mass.

[0040] According to the resin composition of the present invention, since the ethylene-vinyl acetate copolymer (I) and the hydrogenated block copolymer (II) are used in specific blending amounts, when the resin composition is formed into a molded article, a molded article having excellent dry grip and wet grip can be obtained.

[0041] <Ethylene-vinyl acetate copolymer (I)>

[0042] In the present invention, the content of the structural unit derived from vinyl acetate in the ethylene-vinyl acetate copolymer (I) used is preferably 5 to 60% by mass, more preferably 5 to 55% by mass, and further preferably 10 to 50% by mass. When the content of the structural unit derived from vinyl acetate in the ethylene-vinyl acetate copolymer is within the above range, a molded product having excellent dry grip and wet grip can be easily obtained.

[0043] The SP value of the ethylene-vinyl acetate copolymer (I) is preferably 4.0 to 10.0 (cal / cm 3 ) 1 / 2 , more preferably 5.0 to 9.5 (cal / cm 3 ) 1 / 2 , more preferably 6.0 to 9.0 (cal / cm 3 ) 1 / 2 , and more preferably 7.0 to 9.0 (cal / cm 3 ) 1 / 2When the SP value of the ethylene-vinyl acetate copolymer (I) is within the above range, the compatibility with the hydrogenated block copolymer (II) can be easily improved, and the dry grip and wet grip of the molded article can be improved.

[0044] It should be noted that in the present invention, the SP value (solubility parameter) is a value calculated based on the estimation method of DW Van Krevelen, which is a method of calculation based on cohesive energy density and molar molecular volume (DW Van Krevelen, Klaas te Nijenhuis, "Properties of Polymers, Fourth Edition" Elsevier Science, 2009).

[0045] The MFR (melt flow rate) of the ethylene-vinyl acetate copolymer (I) at a temperature of 190° C. and a load of 2.16 kg is preferably 0.5 to 20.0 g / 10 min, more preferably 1.0 to 15.0 g / 10 min, and even more preferably 1.2 to 10.0 g / 10 min. When the MFR is within the above range, the foaming property becomes good.

[0046] It should be noted that the ethylene-vinyl acetate copolymer (I) used in the present invention includes, in addition to ethylene and vinyl acetate, a copolymer containing vinyl alcohol produced by partially hydrolyzing vinyl acetate. In this case, the vinyl acetate content is defined as the total amount of vinyl acetate and vinyl alcohol in the copolymer to limit the vinyl acetate content.

[0047] Examples of commercially available products of the ethylene-vinyl acetate copolymer (I) that can be used in the present invention include “EBAFREX” (trade name, registered trademark) manufactured by Mitsui & Dawu Polychem Co., Ltd., “ULTRACEN” (trade name, registered trademark) manufactured by Tosoh Corporation, “UBE PolyEtrien” (trade name, registered trademark) manufactured by Ube Industries, Ltd., “SANTEC” (trade name, registered trademark) manufactured by Asahi Kasei Chemicals Corporation, and “ETHYLENE VINYL ACETATE COPOLYMER NUC” (trademark) manufactured by NUC Corporation.

[0048] <Hydrogenated block copolymer (II)>

[0049] In the present invention, the hydrogenated block copolymer (II) used is a hydrogenated product of a block copolymer (P) comprising a polymer block (A) comprising a structural unit derived from an aromatic vinyl compound and a polymer block (B) comprising 1 to 100% by mass of a structural unit (b1) derived from farnesene and 99 to 0% by mass of a structural unit (b2) derived from a conjugated diene other than farnesene, wherein the hydrogenation rate of carbon-carbon double bonds in the structural unit derived from the conjugated diene in the block copolymer (P) is 70 mol% or more.

[0050] In the present invention, by using the hydrogenated block copolymer, it is possible to obtain a resin composition capable of providing a molded body having excellent dry grip properties and wet grip properties.

[0051] [Polymer block (A)]

[0052] Examples of the aromatic vinyl compound constituting the polymer block (A) include styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 4-tert-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, N,N-diethyl-4-aminoethylstyrene, vinylpyridine, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, and divinylbenzene. These aromatic vinyl compounds may be used alone or in combination of two or more.

[0053] Among them, styrene, α-methylstyrene, and 4-methylstyrene are more preferred, and styrene is further preferred.

[0054] The peak molecular weight (Mp) of the polymer block (A) is preferably 5000 to 100000, more preferably 6000 to 75000, and even more preferably 7000 to 50000. When the peak molecular weight (Mp) of the polymer block (A) composed of structural units derived from styrene is within the above range, the resin composition can be provided with a molded product having improved workability during production and excellent dry grip and wet grip.

[0055] In addition, the peak molecular weight (Mp) in this specification means the value measured by the method described in the Examples mentioned later.

[0056] It should be noted that all “peak molecular weights” described in the present specification and claims are peak molecular weights calculated in terms of standard polystyrene obtained by gel permeation chromatography (GPC), and more specifically, are values ​​measured by the method described in the Examples.

[0057] The peak molecular weight of each polymer block possessed by the block copolymer (P) can be obtained by measuring the liquid sampled at the end of each polymerization of each polymer block in the manufacturing process. For example, when a triblock copolymer having an a1-b-a2 structure is synthesized by sequentially polymerizing a1, b, and a2, the peak molecular weight of the initial polymer block a1 can be obtained by GPC determination of the liquid sampled at the end of the polymerization of a1. In addition, the peak molecular weight of polymer block b can be obtained as follows: the peak molecular weight of the diblock copolymer having the structure of a1-b is obtained by GPC determination of the liquid sampled at the end of the polymerization of b, and the peak molecular weight of the polymer block a1 is obtained by subtracting the peak molecular weight of the polymer block a1 from the value thereof. Furthermore, the peak molecular weight of polymer block a2 can be obtained as follows: the peak molecular weight of the triblock copolymer having the structure of a1-b-a2 is obtained by GPC determination of the liquid sampled at the end of the polymerization of a2, and the peak molecular weight of the diblock copolymer having the structure of a1-b is obtained by subtracting the peak molecular weight of the diblock copolymer having the structure of a1-b from the value thereof.

[0058] [Polymer block (B)]

[0059] The polymer block (B) contains 1 to 100% by mass of a structural unit (b1) derived from farnesene and 99 to 0% by mass of a structural unit (b2) derived from a conjugated diene other than farnesene.

[0060] The farnesene constituting the farnesene-derived structural unit (b1) may be α-farnesene or β-farnesene represented by the following formula (I), but β-farnesene is preferably used from the viewpoint of the ease of production of the hydrogenated block copolymer. α-farnesene and β-farnesene may be used in combination.

[0061] [Chemistry 1]

[0062]

[0063] Examples of the conjugated diene constituting the structural unit (b2) derived from the conjugated diene other than farnesene include butadiene, isoprene, 2,3-dimethylbutadiene, 2-phenyl-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 1,3-octadiene, 1,3-cyclohexadiene, 2-methyl-1,3-octadiene, 1,3,7-octatriene, myrcene, and chloroprene. These can be used alone or in combination of two or more. Among them, at least one selected from butadiene, isoprene, and myrcene is preferred.

[0064] The polymer block (B) in the present invention contains 1 to 100% by mass of a structural unit (b1) derived from farnesene and 99 to 0% by mass of a structural unit (b2) derived from a conjugated diene other than farnesene. When the content of each structural unit is within the above range, the dry grip and wet grip of the obtained molded article are improved.

[0065] From this viewpoint, the content of the structural unit (b1) derived from farnesene is more preferably 30 to 100% by mass, further preferably 50 to 100% by mass, and further preferably 70 to 100% by mass.

[0066] On the other hand, the content of the structural unit (b2) derived from a conjugated diene other than farnesene is more preferably 0 to 70% by mass, further preferably 0 to 50% by mass, and further preferably 0 to 30% by mass.

[0067] The mass ratio [(A) / (B)] of the polymer block (A) to the polymer block (B) is preferably 10 / 90 to 40 / 60. When the content of the polymer block (A) is above the lower limit, a hydrogenated block copolymer having excellent flexibility and molding processability can be obtained. On the other hand, when the mass ratio is below the upper limit, the compatibility and molding processability with the ethylene-vinyl acetate copolymer (I) are improved. From this viewpoint, the mass ratio [(A) / (B)] of the polymer block (A) to the polymer block (B) is more preferably 15 / 85 to 35 / 65, and further preferably 15 / 85 to 30 / 70.

[0068] 〔Polymer block (C)〕

[0069] The hydrogenated block copolymer (II) obtained by hydrogenating the block copolymer (P) preferably contains, in addition to the aforementioned polymer block (A) and polymer block (B), a polymer block (C) containing a structural unit derived from a conjugated diene other than farnesene.

[0070] The polymer block (C) in the present invention preferably contains less than 1% by mass of a structural unit derived from farnesene and contains 1 to 100% by mass of a structural unit derived from a conjugated diene other than farnesene.

[0071] Examples of the conjugated diene other than farnesene constituting the polymer block (C) include the same conjugated dienes other than farnesene constituting the polymer block (B) described above.

[0072] Among them, the conjugated diene constituting the polymer block (C) is preferably isoprene, butadiene, and myrcene, and more preferably isoprene and butadiene.

[0073] The content of the structural unit derived from the conjugated diene other than farnesene in the polymer block (C) is preferably 60 to 100% by mass, more preferably 80 to 100% by mass, further preferably 90 to 100% by mass, and further preferably substantially 100% by mass, that is, it is composed only of the structural unit derived from the conjugated diene other than farnesene. It should be noted that the content of the structural unit derived from farnesene in the polymer block (C) is preferably 0% by mass.

[0074] In addition, the polymer block (C) may include structural units other than the structural unit derived from farnesene and the structural unit derived from a conjugated diene other than farnesene.

[0075] Examples of monomers constituting the other structural units include unsaturated hydrocarbon compounds such as propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene; unsaturated compounds containing functional groups such as acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, acrylonitrile, methacrylonitrile, maleic acid, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacrylamide-2-methylpropanesulfonic acid, vinyl sulfonic acid, vinyl acetate, and methyl vinyl ether; and the like.

[0076] In the polymer block (C), the total content of the structural unit derived from farnesene and the structural unit derived from a conjugated diene other than farnesene is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 100% by mass.

[0077] [Connection method]

[0078] The hydrogenated block copolymer (II) is a hydrogenated product of a block copolymer (P) comprising at least one each of a polymer block (A) and a polymer block (B), and may contain a polymer block (C) as necessary.

[0079] The connection method of polymer block (A), polymer block (B) and polymer block (C) is not particularly limited, and may be linear, branched, radial or a combination of two or more thereof. Among them, it is preferred that each block is connected in a linear chain. When polymer block (A) is represented by a, polymer block (B) is represented by b, and polymer block (C) is represented by c, it is preferred that (ab) l 、a-(ba) m 、b-(ab) nIt should be noted that the aforementioned l, m and n each independently represent an integer greater than 1.

[0080] In addition, when the block copolymer (P) has two or more polymer blocks (A) or two or more polymer blocks (B), each polymer block may be a polymer block formed by the same structural unit or a polymer block formed by different structural units. For example, in the two polymer blocks (A) in the triblock copolymer represented by [aba], the types of the aromatic vinyl compounds in each of them may be the same or different.

[0081] The hydrogenated block copolymer (II) may be a block polymer of the same type connected in a linear chain via a bifunctional coupling agent, etc. For example, the copolymer represented by bacab may be a copolymer represented by bacxcab (x represents a coupling residue) in which copolymers represented by bac are coupled to each other. In this case, the portion represented by cxc is regarded as one block c.

[0082] Examples of the coupling agent include alkoxysilane compounds such as diethoxydimethylsilane, trimethoxymethylsilane, triethoxymethylsilane, tetramethoxysilane, tetraethoxysilane, tetrabutoxysilane, tetra(2-ethylhexyloxy)silane, bis(triethoxysilyl)ethane, and 3-aminopropyltriethoxysilane; divinylbenzene; polyvalent epoxy compounds such as epoxidized 1,2-polybutadiene, epoxidized soybean oil, and tetraglycidyl-1,3-bis(aminomethyl)cyclohexane; and halogen compounds such as tin tetrachloride, tetrachlorosilane, trichlorosilane, trichloromethylsilane, dichlorodimethylsilane, and dibromodimethylsilane.

[0083] The peak molecular weight (Mp) of the hydrogenated block copolymer (II) is preferably 50,000 to 500,000, more preferably 70,000 to 400,000, further preferably 90,000 to 300,000, and further preferably 100,000 to 250,000, from the viewpoint of improving molding processability. It should be noted that the peak molecular weight (Mp) in this specification refers to a value measured by the method described in the Examples described below.

[0084] The molecular weight distribution (Mw / Mn) of the hydrogenated block copolymer (II) is preferably 1.00 to 4.00, more preferably 1.00 to 3.00, and even more preferably 1.00 to 2.00. When the molecular weight distribution is within the above range, the hydrogenated block copolymer (II) has a small viscosity variation and is easy to handle.

[0085] <Method for producing hydrogenated block copolymer (II)>

[0086] The hydrogenated block copolymer (II) can be preferably produced by, for example, a polymerization step of obtaining a block copolymer (P) by anionic polymerization and a step of hydrogenating carbon-carbon double bonds in the polymer block (B) and the polymer block (C) in the block copolymer (P).

[0087] 〔Polymerization process〕

[0088] The block copolymer (P) can be produced by a solution polymerization method or the method described in Japanese Patent Table 2012-502135 Gazette, Japanese Patent Table 2012-502136 Gazette, etc. Preferably, the solution polymerization method is used, and known methods such as anionic polymerization or cationic polymerization, free radical polymerization, etc. are applicable. Preferably, the anionic polymerization method is used. As the anionic polymerization method, an aromatic vinyl compound, farnesene and / or a conjugated diene other than farnesene are added in sequence in the presence of a solvent, an anionic polymerization initiator, and a Lewis base as required to obtain the block copolymer (P).

[0089] Examples of anionic polymerization initiators include alkali metals such as lithium, sodium, and potassium; alkaline earth metals such as beryllium, magnesium, calcium, strontium, and barium; lanthanide rare earth metals such as lanthanum and neodymium; and compounds containing the above alkali metals, alkaline earth metals, and lanthanide rare earth metals. Among them, alkali metals and compounds containing alkali metals are preferred, and organic alkali metal compounds are more preferred.

[0090] Examples of the organic alkali metal compound include organic lithium compounds such as methyl lithium, ethyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, hexyl lithium, phenyl lithium, distyrene lithium, dilithium methane, dilithium naphthalene, 1,4-dilithium butane, 1,4-dilithium-2-ethylcyclohexane, 1,3,5-trilithium benzene, and the like; sodium naphthyl, potassium naphthyl, and the like. Among them, organic lithium compounds are preferred, and n-butyl lithium and sec-butyl lithium are more preferred, and sec-butyl lithium is particularly preferred. It should be noted that the organic alkali metal compound can be reacted with a secondary amine such as diisopropylamine, dibutylamine, dihexylamine, and dibenzylamine to be used as an organic alkali metal amide.

[0091] The amount of the organic alkali metal compound used for the polymerization varies depending on the molecular weight of the block copolymer (P), but is generally in the range of 0.01 to 3% by mass based on the total amount of the aromatic vinyl compound, farnesene and conjugated diene other than farnesene.

[0092] As the solvent, there is no particular limitation as long as it has no adverse effect on the anionic polymerization reaction, and examples thereof include saturated aliphatic hydrocarbons such as n-pentane, isopentane, n-hexane, n-heptane, isooctane, etc.; saturated alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc., etc. These can be used alone or in combination of two or more. The amount of the solvent used is not particularly limited.

[0093] Lewis base has the function of controlling the microstructure in the structural unit derived from farnesene and the structural unit derived from conjugated diene other than farnesene. Examples of the Lewis base include ether compounds such as dibutyl ether, diethyl ether, tetrahydrofuran, dioxane, ethylene glycol diethyl ether, di(tetrahydrofuranyl)propane, pyridine, tertiary amines such as N,N,N',N'-tetramethylethylenediamine and trimethylamine, alkali metal alkoxides such as potassium tert-butoxide, phosphine compounds, etc. When a Lewis base is used, its amount is usually preferably in the range of 0.01 to 1000 molar equivalents relative to 1 mole of the anionic polymerization initiator.

[0094] The temperature of the polymerization reaction is usually -80 to 150°C, preferably 0 to 100°C, and more preferably in the range of 10 to 90°C. The polymerization reaction may be carried out in a batch or continuous manner. The block copolymer (P) can be produced by continuously or intermittently supplying each monomer in the polymerization reaction solution in such a manner that the amount of the aromatic vinyl compound, farnesene and / or conjugated diene other than farnesene in the polymerization reaction system is within a specific range, or by sequentially polymerizing in such a manner that each monomer is in a specific ratio in the polymerization reaction solution.

[0095] The polymerization reaction can be terminated by adding an alcohol such as methanol or isopropanol as a polymerization terminator. The obtained polymerization reaction liquid can be injected into a poor solvent such as methanol to precipitate the block copolymer (P), or the polymerization reaction liquid can be washed with water, separated, and then dried to separate the block copolymer (P).

[0096] In this polymerization step, an unmodified block copolymer (P) can be obtained as described above, but before the hydrogenation step described below, a block copolymer (P) modified by introducing a functional group into the block copolymer (P) can also be obtained. Examples of the functional group that can be introduced include amino, alkoxysilyl, hydroxyl, epoxy, carboxyl, carbonyl, mercapto, isocyanate, chloro, and acid anhydride.

[0097] As a method for modifying the block copolymer (P), for example, before adding a polymerization terminator, a modifying agent such as tin tetrachloride, tetrachlorosilane, dichlorodimethylsilane, dimethyldiethoxysilane, tetramethoxysilane, tetraethoxysilane, 3-aminopropyltriethoxysilane, tetraglycidyl-1,3-bisaminomethylcyclohexane, 2,4-toluene diisocyanate, 4,4'-bis(diethylamino)benzophenone, N-vinylpyrrolidone, etc., which can react with the polymerization active terminal, or other modifying agents described in Japanese Patent Application Laid-Open No. 2011-132298 can be mentioned. In addition, maleic anhydride or the like can be grafted onto the separated copolymer for use.

[0098] The position where the functional group is introduced may be the polymerization end of the block copolymer (P) or the side chain. In addition, the functional group may be a single type or a combination of two or more types. The modifier is preferably used in an amount of 0.01 to 10 molar equivalents relative to the anionic polymerization initiator.

[0099] 〔Hydrogenation process〕

[0100] A hydrogenated block copolymer (II) can be obtained by imparting a process of hydrogenating the block copolymer (P) or the modified block copolymer (P) obtained by the above method. A known method can be used for the hydrogenation method. For example, a block copolymer (P) is dissolved in a solvent that has no effect on the hydrogenation reaction to form a solution, in which a Ziegler catalyst; a nickel, platinum, palladium, ruthenium or rhodium metal catalyst supported on carbon, silica, diatomaceous earth, etc.; an organic metal complex having cobalt, nickel, palladium, rhodium or ruthenium metal, etc. are present as a hydrogenation catalyst to carry out a hydrogenation reaction. In the hydrogenation step, a hydrogenation catalyst can be added to a polymerization reaction liquid containing a block copolymer (P) obtained by the above-mentioned method for producing a block copolymer (P), and a hydrogenation reaction is carried out. In the present invention, it is preferred that palladium carbon is supported on carbon.

[0101] In the hydrogenation reaction, the hydrogen pressure is preferably 0.1 to 20 MPa, the reaction temperature is preferably 100 to 200° C., and the reaction time is preferably 1 to 20 hours.

[0102] The hydrogenation rate of carbon-carbon double bonds in the hydrogenated block copolymer (II) is preferably 70 to 100 mol%, more preferably 80 to 100 mol%, further preferably 85 to 100 mol%, and further preferably 90 to 100 mol%, from the viewpoint of obtaining a thermoplastic elastomer composition having excellent flexibility and molding processability. 1 It was calculated by H-NMR.

[0103] The SP value of the hydrogenated block copolymer (II) is preferably 6.0 to 10.0 (cal / cm 3 ) 1 / 2 , more preferably 7.0 to 9.5 (cal / cm 3 ) 1 / 2 , more preferably 8.0 to 9.0 (cal / cm 3 ) 1 / 2 When the SP value of the hydrogenated block copolymer (II) is within the above range, the compatibility with the ethylene-vinyl acetate copolymer (I) is improved, and the dry grip and wet grip of the obtained molded article are improved.

[0104] <Contents of ethylene-vinyl acetate copolymer (I) and hydrogenated block copolymer (II)>

[0105] The content of the ethylene-vinyl acetate copolymer (I) in the resin composition is 40 to 95% by mass, and the content of the hydrogenated block copolymer (II) is 5 to 60% by mass. In the present invention, by setting the contents of the ethylene-vinyl acetate copolymer (I) and the hydrogenated block copolymer (II) to the above ranges, a resin composition capable of providing a molded body having excellent dry grip and wet grip can be obtained.

[0106] From the viewpoint of improving the dry grip and wet grip of the molded article, the content of the ethylene-vinyl acetate copolymer (I) in the resin composition is preferably 40 to 95% by mass, more preferably 45 to 95% by mass.

[0107] On the other hand, from the same viewpoint, the content of the hydrogenated block copolymer (II) is preferably 5 to 60% by mass, more preferably 5 to 55% by mass.

[0108] The total content of the ethylene-vinyl acetate copolymer (I) and the hydrogenated block copolymer (II) in the resin composition of the present invention is preferably 50 to 95% by mass, more preferably 70 to 95% by mass, and even more preferably 80 to 95% by mass, from the viewpoint of being able to further improve the anti-slip properties and abrasion resistance of the obtained molded article and also improving the balance between flexibility and processability.

[0109] <Optional ingredients>

[0110] 〔Other resins〕

[0111] The resin composition of the present invention may contain a resin other than the above-mentioned ethylene-vinyl acetate copolymer (I) and the above-mentioned hydrogenated block copolymer (II).

[0112] Examples of the resin other than the ethylene-vinyl acetate copolymer (I) and the hydrogenated block copolymer (II) include thermoplastic elastomer resins and polyolefin-based resins.

[0113] Examples of the thermoplastic elastomer include styrene-based elastomers, olefin-based elastomers, diene-based elastomers, polyvinyl chloride-based thermoplastic elastomers, chlorinated polyethylene-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, and fluororesin-based thermoplastic elastomers.

[0114] Examples of the polyolefin resin include polyethylene such as linear low-density polyethylene and high-density polyethylene. Among them, linear low-density polyethylene is preferred from the viewpoint of improving compatibility with the ethylene-vinyl acetate copolymer (I).

[0115] As the olefin-based elastomer, preferably, there is used a thermoplastic elastomer obtained by finely dispersing ethylene-propylene rubber (EPDM, EPM) in polyisobutylene, ethylene-propylene copolymer, ethylene-propylene-diene terpolymer, or polypropylene (PP).

[0116] Examples of commercially available products of the thermoplastic elastomer and the polyolefin-based resin include ENGAGE 8480 (polyolefin elastomer, manufactured by The Dow Chemical Company) and STN 7006 (Bio LDPE, manufactured by Braskem).

[0117] When the resin composition of the present invention contains other resins, the content thereof is preferably 5 to 80 parts by mass, more preferably 10 to 75 parts by mass, and even more preferably 15 to 70 parts by mass, relative to 100 parts by mass of the total of the ethylene-vinyl acetate copolymer (I) and the hydrogenated block copolymer (II). When the content of the other resin is within the above range, in addition to improving dry grip and wet grip, abrasion resistance and flexibility can also be improved.

[0118] 〔Cross-linking agent〕

[0119] The resin composition of the present invention preferably contains a crosslinking agent. As the crosslinking agent, it is preferred that a substance undergoes a crosslinking reaction only at the carbon-carbon double bond or its α-methylene group in the structural unit derived from the conjugated diene. Here, α-methylene means a methylene group adjacent to the carbon-carbon double bond. By containing such a crosslinking agent, only the above-mentioned carbon-carbon double bond or the α-methylene group of the above-mentioned carbon-carbon double bond in the block copolymer (II) is crosslinked, and a substance that is difficult to slide and has excellent wear resistance while maintaining excellent flexibility can be formed.

[0120] Examples of the crosslinking agent include radical generators, sulfur, and sulfur-containing compounds. From the viewpoint of improving the wear resistance of the molded body, radical generators are more preferred.

[0121] Examples of the free radical generator include organic peroxides such as diisopropylbenzene peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, α,α′-bis(tert-butylperoxy)diisopropylbenzene, 3,3,5-trimethylcyclohexane, n-butyl 4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl carbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide. These organic peroxides may be used alone or in combination of two or more.

[0122] Examples of commercially available products of the radical generator include Percumyl D-40 (dicumyl peroxide, purity 40% by mass, manufactured by NOF Corporation).

[0123] Sulfur can be used without particular limitation, and for example, any of fine sulfur, precipitated sulfur, colloidal sulfur, and insoluble sulfur may be used.

[0124] Examples of the sulfur-containing compound include sulfur monochloride, sulfur dichloride, disulfide compounds, and triazine thiols.

[0125] As the crosslinking agent, other phenolic resins such as alkylphenolic resins and brominated alkylphenolic resins; combinations of p-benzoquinone dioxime and lead dioxide, and p,p'-dibenzoylbenzoquinone dioxime and lead tetraoxide, etc. can be used.

[0126] When the resin composition of the present invention contains a crosslinking agent, the content thereof is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 1.0 to 8 parts by mass, relative to 100 parts by mass of the total of the ethylene-vinyl acetate copolymer (I) and the hydrogenated block copolymer (II). When the content of the crosslinking agent is within the above range, the wear resistance of the obtained molded body and the hardness of the molded body can be improved.

[0127] 〔Cross-linking accelerator〕

[0128] The resin composition of the present invention may also contain a crosslinking accelerator. Examples of the crosslinking accelerator include thiazoles such as N,N-diisopropyl-2-benzothiazole-sulfenamide, 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and 2-(4-morpholinyl dithio)benzothiazole; guanidines such as diphenylguanidine and triphenylguanidine; aldehyde-amine reactants or aldehyde-ammonia reactants such as butyraldehyde-aniline reactants and hexamethylenetetramine-acetaldehyde reactants; imidazolines such as 2-mercaptoimidazoline; diphenylthiourea, diethyl urea Thioureas such as dibutylthiourea, trimethylthiourea, and di-o-tolylthiourea; thiuram monosulfide or polysulfide such as tetramethylthiuram monosulfide, tetramethylthiuram disulfide, and pentamethylenethiuram tetrasulfide; thiocarbamates such as zinc dimethyldithiocarbamate, zinc ethylphenyldithiocarbamate, sodium dimethyldithiocarbamate, selenium dimethyldithiocarbamate, and tellurium diethyldithiocarbamate; xanthates such as zinc dibutylxanthate, etc. These crosslinking accelerators can be used alone or in combination of two or more.

[0129] The content of the crosslinking accelerator is preferably 0.05 to 15 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.5 to 4 parts by mass, based on 100 parts by mass of the total of the ethylene-vinyl acetate copolymer (I) and the block copolymer (II).

[0130] 〔Crosslinking aid〕

[0131] The resin composition of the present invention may further contain a crosslinking aid. Examples of the crosslinking aid include fatty acids such as stearic acid, metal oxides such as zinc flower, and fatty acid metal salts such as zinc stearate. These may be used alone or in combination of two or more.

[0132] When the crosslinking aid is contained, the content thereof is preferably 0.1 to 15 parts by mass, more preferably 1 to 10 parts by mass, based on 100 parts by mass of the total of the ethylene-vinyl acetate copolymer (I) and the hydrogenated block copolymer (II).

[0133] 〔filler〕

[0134] The resin composition of the present invention may also contain fillers other than the above-mentioned silica. As the aforementioned filler, inorganic fillers and / or organic fillers may be utilized. As preferred inorganic fillers, silicate compounds and metal oxides are preferably listed. The silicate compound is preferably selected from one or more silicate compounds of kaolin, talc, clay, pyrophyllite, mica, montmorillonite, bentonite, wollastonite, sepiolite, xonotlite, zeolite, diatomaceous earth, and halloysite. In addition, the metal oxide is selected from one or more metal oxides of titanium oxide, iron oxide, magnesium oxide, aluminum oxide, cerium oxide, antimony oxide, tin oxide, lead oxide, chromium oxide, cobalt oxide, tungsten oxide, and copper oxide.

[0135] In addition, as preferred organic fillers, microparticle-type organic fillers and / or fiber-type organic fillers can be cited. As preferred examples of the aforementioned microparticle-type organic fillers, at least one organic filler selected from urethane microparticles, acrylic microparticles, styrene microparticles, acrylic / styrene microparticles, styrene olefin microparticles, fluorine-based microparticles, polyethylene microparticles and silicone microparticles can be cited. From the viewpoint of the moldability of the resin composition, the preferred average particle size of the aforementioned microparticle-type organic filler is 2 to 50 μm. It should be noted that the average particle size can be measured using a laser diffraction method according to JIS Z 8825-1.

[0136] As the fibrous organic filler, various organic fibers can be used, and preferred examples include synthetic fibers such as 6-nylon fiber, 6,6-nylon fiber, 4,6-nylon fiber, aromatic polyamide fiber, para-aramid fiber, meta-aramid fiber, polyethylene terephthalate (PET) fiber, polyethylene naphthalate (PEN) fiber, poly(p-phenylenebenzoxazole) (PBO) fiber, PVA fiber (vinylon), polyarylene sulfide fiber, 2,6-hydroxynaphthoic acid / parahydroxybenzoic acid fiber (Vectran), polyethylene (PE) fiber, polypropylene (PP) fiber, polylactic acid (PLA) fiber, polybutylene succinate (PBS) fiber, polyethylene succinate fiber, syndiotactic-1,2-polybutadiene (SPB) fiber, polyvinyl chloride (PVC) fiber, and natural (regenerated) fibers such as cotton, linen, rayon, and cellulose fiber.

[0137] When the resin composition of the present invention contains a filler, the content thereof is preferably 1 to 50 parts by mass, more preferably 2 to 20 parts by mass, based on 100 parts by mass of the total content of the ethylene-vinyl acetate copolymer (I) and the block copolymer (II).

[0138] 〔Softener〕

[0139] The resin composition of the present invention may contain a softener within the range that does not impair the effects of the invention. It should be noted that oil-based softeners such as paraffin-based, cycloparaffin-based, and aromatic-based process oils, mineral oils, and white oils are preferably not contained in the resin composition because there is a concern that oil may ooze out over time when the molded body is formed.

[0140] As softeners that may be contained, there may be mentioned, for example, phthalic acid derivatives such as dioctyl phthalate and dibutyl phthalate; liquid copolymers of ethylene and α-olefins; liquid paraffin; polybutene; low molecular weight polyisobutylene; liquid polydienes such as liquid polybutadiene, liquid polyisoprene, liquid polyisoprene / butadiene copolymers, liquid styrene / butadiene copolymers, and liquid styrene / isoprene copolymers, and their hydrogenated products.

[0141] When a softener is contained, the content of the softener in the resin composition is preferably 30% by mass or less, more preferably 20% by mass or less, and further preferably 0% by mass, that is, preferably no softener is contained.

[0142] 〔Other additives〕

[0143] In the resin composition of the present embodiment, other additives other than the above substances may be added within the range that does not impair the effects of the present invention, such as heat aging inhibitors, antioxidants, light stabilizers, antistatic agents, mold release agents, flame retardants, foaming agents, pigments, dyes, whitening agents, etc. These additives may be used alone or in combination of two or more.

[0144] <Biomass ratio>

[0145] The biomass ratio of the resin composition of the present invention is preferably 4 to 70% by mass, more preferably 10 to 60% by mass, and further preferably 15 to 50% by mass. When the biomass ratio is within the above range, environmentally friendly materials can be used, thereby reducing manufacturing costs, and a molded body with excellent dry grip and wet grip can be obtained.

[0146] In addition, in this specification, the biomass ratio means the value measured according to ASTM D6866, and can be measured specifically by the method described in the Examples.

[0147] <Method for producing resin composition>

[0148] The resin composition can be produced by, for example, melt-kneading the components other than the above-mentioned crosslinking agent which is added as necessary, adding the crosslinking agent, and crosslinking by the crosslinking method described below.

[0149] The method for melt-kneading the components other than the cross-linking agent is not particularly limited, and examples thereof include a method in which the ethylene-vinyl acetate copolymer (I), the hydrogenated block copolymer (II) and other arbitrary components are simultaneously supplied to a kneading device such as a single-screw extruder, a multi-screw extruder, a Banbury mixer, a Brabender mixer, an open roll, a heated roll, various kneading machines, etc., and melt-kneaded. Alternatively, there may be a method in which the ethylene-vinyl acetate copolymer (I), the hydrogenated block copolymer (II) and other arbitrary components are supplied from respective feed ports and melt-kneaded, or a method in which the hydrogenated block copolymer (II) and a part of arbitrary components such as silica and a silane coupling agent are preliminarily melt-kneaded and the melt-kneaded product is melt-kneaded with the other arbitrary components.

[0150] The temperature during melt kneading can be arbitrarily selected within the range of 20 to 270°C in general.

[0151] As a cross-linking method, there can be mentioned a method in which after the above-mentioned melt kneading, a cross-linking agent and a cross-linking accelerator are added as needed, a cross-linking mold is used, the cross-linking temperature is usually about 120 to 200° C., preferably 140 to 200° C., and the cross-linking pressure is usually about 0.5 to 10 MPa, and the cross-linking pressure is usually maintained for about 1 minute to 2 hours, thereby cross-linking.

[0152] [Molding body]

[0153] The molded article of the present invention is obtained by using the above-mentioned resin composition, and has excellent dry grip and wet grip. Specifically, the static friction coefficient of the molded article measured according to ASTM D-1894 is preferably 1.5 or more under dry conditions, and more preferably 2.0 or more. In addition, it is preferably 0.7 or more under wet conditions, and more preferably 0.9 or more.

[0154] The dry conditions and wet conditions refer to the measurement conditions described in the Examples described later.

[0155] The shape of the molded body of the present invention can be any shape as long as it can be manufactured using the above-mentioned resin composition, for example, it can be molded into various shapes such as pellets, films, sheets, plates, pipes, tubes, rods, granules, etc. The manufacturing method of the molded body is not particularly limited, and it can be molded by various conventional molding methods, such as injection molding, blow molding, press molding, extrusion molding, calendaring molding, etc. The above-mentioned resin composition is particularly suitable for obtaining a press molded body.

[0156] The molded article can be expected to be difficult to slide and excellent in wear resistance, and can be used for molded products requiring these properties. In particular, it can be suitably used as a molded product such as a shoe sole using at least a part of the resin composition of the present embodiment.

[0157] Specifically, it can be suitably used for: soles for footwear such as hiking boots, sandals, safety shoes, mountaineering shoes, marathon shoes, rubber-soled shoes and long boots; sports equipment such as underwater goggles, snorkels, ski boots and snowboards; writing utensils such as pens and scissors, tools and electrical tools such as screwdrivers, pliers and wrenches, supplies for water places such as toothbrushes and kitchen supplies (kitchen knives and spatulas, etc.), golf clubs, ski poles, bicycles, motorcycles and other utensils for sports and fitness, and various handles for knives, etc.; refrigerators, Parts of household appliances such as vacuum cleaners and waterproof bodies (cellular phones, etc.); automotive products such as side moldings, rack / pinion protection covers, suspension protection covers, constant velocity joint protection covers, weather stripping, pads, floor mats, armrests, wire moldings, flush fittings and automotive interior and exterior (gears and knobs, etc.); office equipment such as copier paper feed rollers and winding rollers; parts used in furniture such as sofa and chair sheets; rubber parts such as switch covers, plugs, casters and rubber pads; building materials such as coated plywood and coated steel plates, etc.

[0158] In addition, the molded article of the present invention is excellent in dry grip and wet grip even if it does not have a silica-containing layer containing silica on the surface of the molded article. Example

[0159] The present invention is described in more detail below by way of examples and comparative examples, but the present invention is not limited to these examples. It should be noted that β-farnesene (purity 97.6% by mass, AMRS, manufactured by Incomoleitide Co., Ltd.) was purified by passing through a 3Å molecular sieve and distilled under a nitrogen atmosphere to remove hydrocarbon impurities such as zingiberene, bisabolene, epoxidized farnesene, farnesol isomers, E,E-farnesol, squalene, ergosterol, and various dimers of farnesene, and was used for the following polymerization.

[0160] <Ethylene-vinyl acetate copolymer (I)>

[0161] ・EV460 (VA = 19% by mass, temperature 190°C, MFR at load 2.16kg = 2.5g / 10min, SP value = 8.30 (cal / cm 3 ) 1 / 2 , Mitsui・ダウポリケミカル Co., Ltd.)

[0162] ・EV45LX (VA = 46% by mass, temperature 190°C, MFR at load 2.16 kg = 2.5 g / 10 min, SP value = 8.60 (cal / cm 3 ) 1 / 2 , Mitsui・ダウポリケミカル Co., Ltd.).

[0163] <Hydrogenated block copolymer (II)>

[0164] ・Hydrogenated block copolymer (II-1)

[0165] The hydrogenated block copolymer (II-1) of Production Example 1 described below

[0166] ・Hydrogenated block copolymer (II-2)

[0167] The hydrogenated block copolymer (II-2) of Production Example 2 described later.

[0168] <Unhydrogenated block copolymer (P')>

[0169] The unhydrogenated block copolymer (P') of Production Example 3 described later.

[0170] <Other resins>

[0171] ・ENGAGE8480 (polyolefin elastomer, manufactured by The Dow Chemical Company)

[0172] ・STN7006 (バイオLDPE, manufactured by Braskem Corporation).

[0173] <Cross-linking agent>

[0174] ・Percumyl D-40 (purity 40% by mass, manufactured by NOF Corporation).

[0175] <Crosslinking aid>

[0176] ・Zinc oxide: Zinc oxide type 1 manufactured by Sakai Chemical Industry Co., Ltd.

[0177] ・Stearic acid: Lunec S-20, manufactured by Kao Corporation.

[0178] [Measurement method]

[0179] The details of each measurement method for the polymers obtained in the Production Examples are as follows.

[0180] (1) Determination of peak molecular weight and molecular weight distribution

[0181] The peak molecular weight of the hydrogenated block copolymer, the peak molecular weight of the styrene block (Mp), and the molecular weight distribution (Mw / Mn) were determined by GPC (gel permeation chromatography) using standard polystyrene-equivalent molecular weights, and the peak molecular weight (Mp) was determined from the top position of the peak of the molecular weight distribution. The measuring apparatus and conditions are as follows.

[0182] ・Device: GPC device "HLC-8320GPC" manufactured by Tosoh Corporation

[0183] ・Separation column: TSKgelSuperHZ4000 manufactured by Tosoh Corporation

[0184] ・Eluent: Tetrahydrofuran

[0185] ・Eluent flow rate: 0.7mL / min

[0186] ・Sample concentration: 5mg / 10mL

[0187] ・Column temperature: 40℃.

[0188] (2) Method for determining hydrogenation rate

[0189] The block copolymer (P) and the hydrogenated block copolymer (II) were dissolved in deuterated chloroform solvent, and the reaction mixture was measured at 50°C using Lambda-500 manufactured by JEOL Ltd. 1 H-NMR.

[0190] The hydrogenation rate of the carbon-carbon double bonds in the structural units derived from the conjugated diene in the hydrogenated block copolymer (II) was calculated by the following formula from the peak of protons in the carbon-carbon double bonds appearing at 4.5 to 6.0 ppm in the obtained spectrum.

[0191] Hydrogenation rate (mol %)={1-(the number of moles of carbon-carbon double bonds contained in 1 mole of the hydrogenated block copolymer (II)) / (the number of moles of carbon-carbon double bonds contained in 1 mole of the block copolymer (P))}×100.

[0192] [Production Example 1]

[0193] Hydrogenated block copolymer (II-1)

[0194] In a nitrogen-purged and dried pressure vessel, 50.0 kg of cyclohexane as a solvent, 0.1905 kg of sec-butyl lithium (10.5 mass % cyclohexane solution) as an anionic polymerization initiator, and 0.40 kg of tetrahydrofuran as a Lewis base were placed, and after heating to 50° C., 6.34 kg of β-farnesene was added, and polymerization was carried out for 2 hours. Subsequently, 2.50 kg of styrene (1) was added, and polymerization was carried out for 1 hour. Further, 3.66 kg of butadiene was added, and polymerization was carried out for 1 hour. Subsequently, 0.02 kg of dichlorodimethylsilane was added to the polymerization reaction solution as a coupling agent, and the reaction was carried out for 1 hour, thereby obtaining a reaction solution containing a poly(β-farnesene)-polystyrene-polybutadiene-polystyrene-poly(β-farnesene) pentablock copolymer (P-1).

[0195] To the reaction solution, 5% by mass of palladium carbon (palladium loading: 5% by mass) as a hydrogenation catalyst was added relative to the block copolymer (P-1), and the reaction was carried out under the conditions of a hydrogen pressure of 2 MPa and 150° C. for 10 hours. After cooling and depressurization, the palladium carbon was removed by filtration, the filtrate was concentrated, and then vacuum dried to obtain a hydrogenated product (II-1) of a poly(β-farnesene)-polystyrene-polybutadiene-polystyrene-poly(β-farnesene) pentablock copolymer (hereinafter referred to as "hydrogenated block copolymer (II-1)"). The biomass ratio of the obtained hydrogenated block copolymer (I-1) measured in accordance with ASTM D6866 was 50% by mass.

[0196] The above-mentioned physical properties of the obtained hydrogenated block copolymer (II-1) were measured. The results are shown in Table 1.

[0197] [Production Example 2]

[0198] Hydrogenated block copolymer (II-2)

[0199] In a nitrogen-purged and dried pressure vessel, 50.0 kg of cyclohexane as a solvent and 0.0413 kg of sec-butyllithium (10.5 mass % cyclohexane solution) as an anionic polymerization initiator were placed, and after heating to 50° C., 1.12 kg of styrene (1) was added, and polymerization was carried out for 1 hour, followed by the addition of 10.25 kg of β-farnesene, and the addition of 1.12 kg of styrene (2), and the polymerization was carried out for 1 hour to obtain a reaction solution containing a polystyrene-poly(β-farnesene)-polystyrene triblock copolymer (P-2). To the reaction solution, 5 mass % of palladium carbon (palladium loading: 5 mass %) as a hydrogenation catalyst was added relative to the block copolymer (P-2), and the reaction was carried out at a hydrogen pressure of 2 MPa and 150° C. for 10 hours. After cooling and depressurization, palladium carbon was removed by filtration, and the filtrate was concentrated and then vacuum dried to obtain a hydrogenated product of a polystyrene-poly(β-farnesene)-polystyrene triblock copolymer (hereinafter referred to as "hydrogenated block copolymer (I-2)"). The biomass ratio of the obtained hydrogenated block copolymer (II-2) measured according to ASTM D6866 was 82% by mass. The above-mentioned physical properties of the hydrogenated block copolymer (II-2) were measured. The results are shown in Table 1.

[0200] [Production Example 3]

[0201] Unhydrogenated block copolymer (P')

[0202] Into a nitrogen-purged and dried pressure vessel, 50.0 kg of cyclohexane as a solvent and 0.073 kg of sec-butyllithium (10.5 mass % cyclohexane solution) as an anionic polymerization initiator were placed, and after heating to 50° C., 1.25 kg of styrene (1) was added and polymerization was carried out for 1 hour. 0.27 kg of tetrahydrofuran as a Lewis base was added, followed by 10.00 kg of isoprene, and polymerization was carried out for 2 hours. Furthermore, 1.25 kg of styrene (2) was added and polymerization was carried out for 1 hour to obtain a reaction solution containing a styrene-isoprene-styrene triblock copolymer (P′).

[0203] To the reaction solution, 200 mL of methanol was added to terminate the polymerization reaction. The resulting mixed solution was washed with water and then reprecipitated in a large amount of methanol to obtain a styrene-isoprene-styrene triblock copolymer (hereinafter also referred to as "unhydrogenated block copolymer (P')").

[0204] The above-mentioned physical properties were measured for the unhydrogenated block copolymer (P'). The results are shown in Table 1.

[0205] [Table 1]

[0206]

[0207] *1: Indicates the mass ratio of polymer block (A) to polymer block (B).

[0208] *2: It shows the content (mass %) of the structural unit (b1) derived from farnesene in the polymer block (B).

[0209] *3: represents the content (mass %) of the structural unit (b1) derived from farnesene in the polymer block (B) and the polymer block (C).

[0210] *4: F-St-Bd-St-F represents a poly(β-farnesene)-polystyrene-polybutadiene-polystyrene-poly(β-farnesene) pentablock copolymer.

[0211] St-F-St represents a polystyrene-poly(β-farnesene)-polystyrene triblock copolymer.

[0212] St-Ip-St represents a polystyrene-polyisoprene-polystyrene triblock copolymer.

[0213] *4: The hydrogenation rate of the hydrogenated block copolymer (II) indicates the hydrogenation rate of the carbon-carbon double bonds in the structural unit derived from the conjugated diene in the block copolymer (P).

[0214] <Examples 1 to 9, Comparative Examples 1 to 6>

[0215] (1) Melt kneading (production of resin composition)

[0216] According to the compounding ratio (parts by mass) described in Table 3, the mixture was put into a Brabender mixer (product name: Plastic Graph EC50cc mixer, manufactured by Brabender Co., Ltd.) in the order and conditions shown in Table 2 for melt kneading (steps 1 and 2). Then, the melt kneaded product was taken out of the Brabender mixer (step 3). Next, the melt kneaded product was put into the Brabender mixer again and kneaded (step 4), and then a crosslinking agent was added and kneaded again (step 5), thereby obtaining a resin composition.

[0217] (2) Molding (manufacturing of molded products)

[0218] The obtained resin composition was press-molded (170° C., 7 to 10 minutes) to obtain a sheet (thickness 0.5 mm) while being cross-linked.

[0219] The physical properties of the obtained sheet were evaluated according to the following evaluation methods.

[0220] [Table 2]

[0221] .

[0222] <Evaluation Method>

[0223] 〔Static friction coefficient〕

[0224] (1) Drying

[0225] The static friction coefficients of the surfaces of the sheets obtained in Examples and Comparative Examples were measured in accordance with ASTM D-1894.

[0226] A test piece with a length of 110 mm, a width of 63.5 mm, and a thickness of 0.5 mm was cut from the sheet, and wound on an element (weight 200 g, 63.5 mm × 63.5 mm), and fixed to the head of the automatic recorder in a way that the test piece stage of the friction coefficient measuring device is horizontal. The material of the friction table is set to aluminum, and the static friction coefficient is measured at a tensile speed of 150 mm / min. The higher the value of the static friction coefficient, the greater the friction force, the more difficult it is to slide, and the dry grip is excellent.

[0227] (2) Humidity

[0228] The static friction coefficient was measured in the same manner as in the above (1) drying except that 1 cc of distilled water was dropped onto the friction table. The higher the static friction coefficient, the greater the friction force and the less likely it is to slide, indicating excellent wet grip.

[0229] <Biomass ratio>

[0230] Biomass ratio (mass %)

[0231] =(M I ×X I / 100)+(M II ×X II / 100)

[0232] (In the above formula, M I represents the mass ratio (mass %) of the ethylene-vinyl acetate copolymer (I) to the total mass of the ethylene-vinyl acetate copolymer (I) and the hydrogenated block copolymer (II), M II It represents the mass ratio (mass %) of the hydrogenated block copolymer (II) to the total mass of the ethylene-vinyl acetate copolymer (I) and the hydrogenated block copolymer (II). I (%) represents the biomass ratio of ethylene-vinyl acetate copolymer (I), X II (%) represents the biomass ratio of the hydrogenated block copolymer (II). The biomass ratio is measured according to ASTM D6866.

[0233] [Table 3]

[0234] .

[0235] From the results in Table 3, it is understood that the resin composition of the present invention can provide a molded body having excellent dry grip properties and wet grip properties.

Claims

1. A resin composition comprising an ethylene-vinyl acetate copolymer (I) and a hydrogenated block copolymer (II), characterized in that: The content of the structural unit derived from vinyl acetate in the ethylene-vinyl acetate copolymer (I) is 10 to 46% by mass. The hydrogenated block copolymer (II) is a hydrogenated product of a block copolymer (P) comprising a polymer block (A) and a polymer block (B), wherein the polymer block (A) comprises a structural unit derived from an aromatic vinyl compound, the polymer block (B) comprises 1 to 100% by mass of a structural unit (b1) derived from farnesene and 99 to 0% by mass of a structural unit (b2) derived from a conjugated diene other than farnesene, and the hydrogenation rate of carbon-carbon double bonds in the structural unit derived from the conjugated diene in the block copolymer (P) is 70 mol% or more, The aforementioned hydrogenated block copolymer (II) is a hydrogenated product of a triblock copolymer, When polymer block (A) is represented by a and polymer block (B) is represented by b, the connection mode of the polymer block (A) and the polymer block (B) is represented by aba. The content of the ethylene-vinyl acetate copolymer (I) in the resin composition is 45 to 95% by mass, and the content of the hydrogenated block copolymer (II) is 5 to 55% by mass.

2. The resin composition according to claim 1, wherein The biomass ratio is 4 to 70% by mass.

3. The resin composition according to claim 1 or 2, wherein The aromatic vinyl compound is styrene.

4. The resin composition according to claim 1 or 2, wherein The conjugated diene other than farnesene is at least one selected from the group consisting of butadiene, isoprene, and myrcene.

5. The resin composition according to claim 1 or 2, wherein The mass ratio (A) / (B) of the polymer block (A) to the polymer block (B) is 10 / 90 to 40 / 60.

6. The resin composition according to claim 1 or 2, wherein The SP value of the ethylene-vinyl acetate copolymer (I) is 4.0 to 10.0 (cal / cm 3 ) 1 / 2 The SP value of the hydrogenated block copolymer (II) is 6.0 to 10.0 (cal / cm 3 )1 / 2.

7. The resin composition according to claim 1 or 2, wherein The peak molecular weight of the hydrogenated block copolymer (II) is 50,000 to 500,000.

8. The resin composition according to claim 1 or 2, wherein The peak molecular weight of the polymer block (A) is 5,000 to 100,000.

9. A molded article, at least a part of which is formed using the resin composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Rubber composition with improved wet gripping property

    JP2003292672A

  • Rubber composition improved in wet gripping property

    JP2004075882A

  • Modified copolymer and rubber composition and pneumatic tire using the same

    JP2011132298A

  • Adhesive composition containing polyfarnesene

    JP2012502135A

  • Farnesene copolymer

    JP2012502136A